2018
DOI: 10.11144/javeriana.upsy17-3.pofe
|View full text |Cite
|
Sign up to set email alerts
|

Protocolo de observación de la función de explicación (PROFE): un instrumento para operacionalizar la transmisión de contenidos por parte del profesorado

Abstract: La calidad de la docencia universitaria es fundamental dentro del proceso educativo, lo que exige la evaluación del profesorado, prefiriéndose la metodología observacional cuando se evalúa la conducta de este. El objetivo de este estudio consistió en el análisis pormenorizado de la función docente de explicación, de especial relevancia dentro el escenario educativo, lo que hace importante su análisis. Para ello, se utilizó el instrumento observacional PROFE, para medir los recursos y estrategias utilizados dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Their results showed that the didactic performance criteria of Illustration -Adjustment to illustration and Exploration of competencies -Adjustment to the exploration were the most significant even though the Feedback -Adjustment to feedback criterion also was presented in both courses but in less proportion. Regarding the didactic performance of the teacher that was called Illustration, which was the less frequent, data in this study matched the findings of Borges and Falcón (2018) with their analysis of the function of a teacher in university-level classes. These authors found that the most frequent teacher performances were Linear explanations and Explanation with materials or resources.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Their results showed that the didactic performance criteria of Illustration -Adjustment to illustration and Exploration of competencies -Adjustment to the exploration were the most significant even though the Feedback -Adjustment to feedback criterion also was presented in both courses but in less proportion. Regarding the didactic performance of the teacher that was called Illustration, which was the less frequent, data in this study matched the findings of Borges and Falcón (2018) with their analysis of the function of a teacher in university-level classes. These authors found that the most frequent teacher performances were Linear explanations and Explanation with materials or resources.…”
Section: Discussionsupporting
confidence: 79%
“…The observational record has been used in different investigations based on both cognitive perspectives and behavioral approaches (Bell et al, 2019;Borges et al, 2016;Gitomer, 2019;Joyce et al, 2018;Peralta & Roselli, 2015;Ruiz et al, 2020;Velarde-Corrales & Bazán, 2019). Thus, studies have reported using observational records of teacher performance categories (Borges & Falcón, 2018;Borges et al, 2016;Díaz et al, 2015) and categories or criteria of teacher and student performance in interactive teaching/learning processes (Galindo et al, 2017;Velarde-Corrales & Bazán, 2019).…”
Section: Introductionmentioning
confidence: 99%